The Emerald handbook of Fintech : reshaping finance - Baker, H. Kent; Filbeck, Greg; Black, Keith (Emerald Publishing Limited, 2024)
The rapidly growing fintech market reflects new technology that seeks to improve and automate the delivery and use of financial services. Regulation changes have provided new opportunities in crowdfunding and peer-to-peer (P2P) lending. At the same time, technological advances have made artificial intelligence (AI) and machine learning (ML) accessible to practitioners without a programming background. New markets in cryptocurrencies and digital assets promise to make finance more global with lower transaction costs and faster transaction processing times. Additionally, robo-advisors and online trading make financial markets more accessible to investors, even those younger or just making their first investments. The Emerald Handbook of Fintech offers a detailed, user-friendly examination of the technologies and products reshaping the financial technology industry from leading global scholars and practitioners. Innovative companies can review the state of the industry in a way that may allow them to envision their role or niche in this fast-growing, ever-evolving industry. Most importantly, incumbent firms can view the rate of change and plan for how they can keep pace with these innovations to profit from change. Given the interplay among rapidly evolving regulations, technologies, and products, academics, practitioners, and students should view fintech's risks and potential opportunities from this holistic perspective.